Increased pain and muscle glutamate concentration after single ingestion of monosodium glutamate by myofascial temporomandibular disorders patients. (18th April 2016) - Shimada, A.; Castrillon, E.E.; Baad‐Hansen, L.; Ghafouri, B.; Gerdle, B.; Wåhlén, K.; Ernberg, M.; Cairns, B.E.; Svensson, P.
Abstract: Background: A randomized, double‐blinded, placebo‐controlled study was conducted to investigate if single monosodium glutamate (MSG) administration would elevate muscle/serum glutamate concentrations and affect muscle pain sensitivity in myofascial temporomandibular disorders (TMD) patients more than in healthy individuals. Methods: Twelve myofascial TMD patients and 12 sex‐ and age‐matched healthy controls participated in two sessions. Participants drank MSG (150 mg/kg) or NaCl (24 mg/kg; control) diluted in 400 mL of soda. The concentration of glutamate in the masseter muscle, blood plasma and saliva was determined before and after the ingestion of MSG or control. At baseline and every 15 min after the ingestion, pain intensity was scored on a 0–10 numeric rating scale. Pressure pain threshold, pressure pain tolerance (PPTol) and autonomic parameters were measured. All participants were asked to report adverse effects after the ingestion. Results: In TMD, interstitial glutamate concentration was significantly greater after the MSG ingestion when compared with healthy controls. TMD reported a mean pain intensity of 2.8/10 at baseline, which significantly increased by 40% 30 min post MSG ingestion. At baseline, TMD showed lower PPTols in the masseter and trapezius, and higher diastolic blood pressure and heart rate than healthy controls. The MSG ingestion resulted in reports of headache by half of the TMD and healthy controls, respectively. Conclusion: These findings suggest that myofascial TMD patients may be particularly sensitive to the effects of ingested MSG. What does this study add?': Elevation of interstitial glutamate concentration in the masseter muscle caused by monosodium glutamate (MSG) ingestion was significantly greater in myofascial myofascial temporomandibular disorders (TMD) patients than healthy individuals. This elevation of interstitial glutamate concentration in the masseter muscle significantly increased the intensity of spontaneous pain in myofascial TMD patients.